Potencial antiaterogênico da bixina in vivo e in vitro - Somacal, Sabrina (2016)
Atherosclerosis is a chronic disease characterized by the accumulation of lipids and fibrous elements in the intima layer of medium and large caliber arteries. Inflammation, oxidative stress as well as low density lipoprotein (LDL) oxidative modification plays an important role in the development of this disease. Thus, the inclusion of antioxidants in the diet may prevent the atherosclerosis progression. The carotenoid bixin, found in annatto seeds, has excellent antioxidant activity as demonstrated in several models of oxidative damage. In this context, the objective of this study was to evaluate the antiatherogenic potential of bixin and the mechanisms involved in this effect in models in vivo and in vitro. First, we evaluated the administration of an atherogenic diet (0.5% cholesterol) alone or supplemented with bixin (10, 30 or 100 mg/kg) or simvastatin (15 mg/kg) for 60 days in New Zealand rabbits. The atherogenic diet increased lipid serum levels, besides inducing lipid oxidation (TBARS) in aortic tissue. Supplementation with bixin or simvastatin (hypocholesterolemic reference drug) reduced serum triglycerides and TBARS levels induced by atherogenic diet in the aortic tissue but only bixin reduced the atherogenic index and increased HDL levels. Supplementation with bixin or simvastatin restored changes in NPSH levels and antioxidant enzymes activity induced by the atherogenic diet. Bixin reduced the serum levels of interleukin 6 (IL -6), tumor necrosis factor (TNF-α) and the ratio between the thickness of the intima and media in the aortic arc. Thus, the in vivo antiatherosclerotic effect of bixin seems to be associated with an improvement in the lipid profile, decreased oxidative stress and inflammatory response and prevention of changes in the antioxidant system. Considering the promising effect of bixin in vivo, in the second part of this study we investigated the possible mechanisms related to antiatherogenic effect of bixin, such as potential to prevent the oxidation of LDL in vitro and the cytotoxic effects of oxidized LDL (oxLDL) in cultured macrophages. Bixin inhibited lipid and protein oxidation of isolated human LDL in a concentration–dependent manner, and was more potent than lycopene. From 0.1 μM onwards, bixin prevented apolipoprotein B-100 (apo B-100) fragmentation, assessed by tryptophan destruction, and from 2.5 μM onwards bixin caused inhibited the formation of conjugated dienes, demonstrating that bixin has direct antioxidant effects Considering the involvement of oxLDL in the pathogenesis of atherosclerosis, we investigated the protective effect of bixin against cytotoxic damage induced by exposure of macrophages J774A.1 to oxLDL (100 μg/mL). Bixin pretreatment for 24 h reduced the cytotoxic effects triggered by oxLDL in J774A.1 macrophages in vitro, including the generation of reactive oxygen and nitrogen species, disturbance in the nitric oxide homeostasis, mitochondrial dysfunction, glutathione depletion and foam cell formation. The probable mechanisms of bixin on signaling pathways have also been investigated in cultured macrophages, demonstrating that the antiatherogenic effects of bixin are related to modulation of antioxidant and anti- inflammatory pathways through activation of Nrf2 and inactivation of NFκB pathways. Taken together, the results of this study indicate that the antiatherogenic effects of bixin are related to the prevention of LDL oxidation, improved lipid profile and cellular redox balance, as well as anti -inflammatory action and a reduction of foam cell formation and atherosclerotic lesions. These data suggest a new role for the carotenoid bixin as a potential anti-atherogenic agent.